Numerical algorithm for the time dependent strongly-out-of-equilibrium Boltzmann equation: numerical methods for spectra - Ching, Trevor Haoye (Nanyang Technological University, 2022)
This thesis details the development of a C++ software library designed to simulate the time-dependent, strongly out-of-equilibrium thermalisation of solid materials upon interaction with a femtosecond laser pulse, specifically the numerical methods used to ultimately construct spectra of realistic 2D materials. The numerical methods for computing the general form of the multidimensional Dirac-delta integral and the convolution integral were implemented, and then applied to the study of the absorption spectrum of 2D monolayer graphene. The thesis also elaborates on the fundamental concepts behind the methods and the troubleshooting process during the implementation of the numerical methods.